Pengaruh Pendapatan, Jumlah Nasabah, Harga Emas Dan Tingkat Inflasi Terhadap Penyaluran Kredit Cepat Aman (Kca) Di Pegadaian Indonesia Tahun 2009-2017 - Yubiharto Yubiharto; Bayu Lestari (Medikonis, 2019)
ABSTRACT The problem in this research is the target Distribution Kredit Cepat Aman (KCA) which has not been realized in the last few years. PT Pegadaian had an internal and eksternal factor in determine Distribution Kredit Cepat Aman (KCA). The aim of this research was to determined the influence of revenue, number of customers, gold price, and inflation rate on Distribution Kredit Cepat Aman (KCA) at PT Pegadaian Indonesia in 2009-2017. The method used seconder research method is obtainable from annual report PT Pegadaian 2009-2017, taken from www.pegadaian.go.id. The population in this research are all annual report PT Pegadaian Indonesian 2009-2017. The dependent variable from this research is Distribution Kredit Cepat Aman (KCA). The independent variable include revenue, number of customers, gold price, and inflation rate. The sample technique of this research was using the all data of those Annual Report. The analysis method used multiple linear regression by software SPSS version 24. The result showed that The revenue have a significant influence to Distribution Kredit Cepat Aman (KCA) at PT Pegadaian Indonesian 2009-2017. The number of customers have a significant influence to Distribution Credit Fast secure (KCA) at PT Pegadaian Indonesian 2009-2017. The gold price customers have a significant influence to Distribution Kredit Cepat Aman (KCA) at PT Pegadaian Indonesian 2009-2017, and inflation rate have a significant influence to Distribution Kredit Cepat Aman (KCA) at PT Pegadaian Indonesian 2009-2017. The simultaneously are revenue, number of customers, gold price, and inflation rate revenue have a significant influence to Distribution Kredit Cepat Aman (KCA) at PT Pegadaian Indonesian 2009-2017.